Determination of a representative food mass-to-surface area ratio (mF/A) for estimating migration values of food contact substances in single use food contact articles marketed in the United States - Zhovmer, Lauren M.; GonzalezBonet, Andres M.; Garg, Madhur; Bailey, Allan B.; Arvidson, Kirk B. (Frontiers in Food Science and Technology, 2024)
When reviewing the safety of food packaging, safety assessors must determine the migration levels of a food contact substance (FCS) from the packaging into the contained food products. Migration values can be expressed relative to levels in food using a single ‘food mass-to-surface area (mF/A) ratio’, representative of the general food supply. Because no published literature has examined mF/A ratios for the current U.S. food supply, this study aimed to use food databases to develop a standard mF/A ratio representative of packaged foods in the current U.S. food supply. First, we obtained information on the food-contact surface area (A) and food mass (mF) for a selection of packaged foods sold in U.S. retail stores. To adequately represent the variation of food products on the market, we identified a representative product per food category, using a 95-category list that was derived from the USDA WWEIA Food Categories. The values for A and mF per package were determined for each representative product using product size information from the Syndigo Nutrition Database. These data were used to calculate the A/mF ratio for each of the 95 representative products, and the average A/mF ratio was determined. The average A/mF ratio was weighted using consumption data from the WWEIA component of NHANES, so that more weight was given to foods that are consumed in greater quantities. The final step was to then take the reciprocal of the averaged A/mF ratio to obtain the final mF/A ratio. The resulting mF/A ratio was 4.8 g/in2, which rounds to 5 g/in2. In summary, we determined that 5 g/in2 is representative of the current U.S. food supply and could be used as a standard mF/A ratio when estimating migration levels of an FCS from packaging into food.